Evaluating the impacts of participatory processes for water management: a theoretical proposal based on the capability approach. (5th May 2022) - Loudin, Sarah; Ferrand, Nils; Garin, Patrice; Pelenc, Jérôme; Bonnard, Sophie
Public participation to manage water resources is largely promoted by institutional actors from national to international scale. Progress is still required to understand, depending on specific variables such as contexts, issues or implementation protocols, how participatory processes impact the individual participants, the group and eventually their decisions and practices. The need for a scientific evaluation tool applied to participatory processes and their transformative impacts has thus emerged during the last decade. We argue in this contribution that the capability approach can support researchers and practitioners in specifying, identifying and understanding changes occurring among individuals and groups taking part in a participatory process because of the twofold link that exists between the capabilities of participants and the participatory process they undertake. Once this has been considered, several methodological choices are required and reviewed here to define an operational evaluation framework, starting with the choice of the relevant capabilities to integrate into it.